CHARACTERISTICS OF SELF‐SIMILARITY OF SEISMICITY AND THE FAULT NETWORK OF THE SIKHOTE ALIN OROGENIC BELT AND THE ADJACENT AREAS - V. S. Zakharov; A. N. Didenko; G. Z. Gil’manova; T. V. Merkulova (Геодинамика и тектонофизика)
We performed a comprehensive analysis of the characteristics of self‐similarity of seismicity and the fault network within the Sikhote Alin orogenic belt and the adjacent areas. It has been established that the main features of seismicity are controlled by the crustal earthquakes. Differentiation of the study area according to the density of earthquake epicenters and the fractal dimension of the epicentral field of earthquakes (De) shows that the most active crustal areas are linked to the Kharpi‐Kur‐Priamurye zone, the northern Bureya massif and the Mongol‐Okhotsk folded system. The analysis of the earthquake recurrence plot slope values reveals that the highest b‐values correlate with the areas of the highest seismic activity of the northern part of the Bureya massif and, to a less extent, of the Mongol‐Okhotsk folded system. The increased fractal dimension values for the fault network (Df) correlate with the folded systems (Sikhote Alin and Mongol‐Okhotsk), while the decreased values conform to the depressions and troughs (Middle Amur, Uda and Torom). A comparison of the fractal analysis results for the fault network with the recent stress‐strain data gives evidence of their general confineness to the contemporary areas of intense compression. The correspondence between the field of the parameter b‐value for the upper crustal earthquakes and the fractal dimension value for the fault network (Df) suggests a general consistency between the self‐similar earthquake magnitude (energy) distribution and the fractal distribution of the fault sizes. The analysis results demonstrate that the selfsimilarity parameters provide an important quantitative characteristic in seismotectonics and can be used for the neotectonic and geodynamic analyses.